The Perceived Consequences of Liveability Among Residents of Cimahi City - Nurzahra, Aprilianti Dewi; Ernawadi, Yadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the impact of liveability on continuance resident commitment, with resident satisfaction and place attachment as mediating variables among residents of Cimahi City. Social exchange theory (SET) is employed as the theoretical foundation for developing the study’s conceptual framework. Data were collected from 140 respondents using a cross-sectional technique. The analysis was conducted using Structural Equation Modelling (SEM) with the application of SmartPLS version 3.0. What distinguishes this study from previous research is the proposed inclusion of four dimensions of liveability comprise social relations, physical residential environment, functional facilities and services, and crime and sense of safety, which are hypothesized to positively influence continuance resident commitment through the mediating effects of resident satisfaction and place attachment. The results indicate that both mediators play a critical role in bridging the relationship between liveability and continuance resident commitment to their locality. These findings offer meaningful insights for the local government of Cimahi in identifying key drivers to enhance sustained continuance resident commitment among citizens of Cimahi.